A linguagem online a favor do desenvolvimento da competência linguística e discursiva do aluno - Gillienne Guimarães Garcia (2018)
A teacher that proposes to teach Portuguese subject to students, who are native Portuguese speakers, assumes, perhaps, a greatest challenge than those who endeavor to teach a foreign language. Learning a second language to a pupil implies novelty, it means everything is new, challenging and relevant, since the learner wants to become fluent in the new language, be able to understand and be understood. It is a new whole world of possibilities that opens ahead of them. However, when it comes to teaching a mother tongue, how can a tutor arouse the same interest in their students, if since their childhood begin in their household core, they already learn almost all what they need to communicate during their lifetime naturally and spontaneously? This questioning has been concerning me, since I entered the Bachelor of Arts major- Portuguese/English, in 2007. In the State University of Minas Gerais (Divinópolis campus) How to teach Portuguese to skilled speakers of this language? How not to give in to social pressure? It is worse, sometimes, even to the educational one to become the Portuguese language education into normative grammar classes purely. It would be easier and convenient to surrender to those pressures and teach only the iceberg tip from a huge language. This paper although represents an attempt that goes against this trend. It is the result of willingness and effort from getting out of the common place. Which means to be out of the box of stagnation, of the mud quagmire, that is the teaching of Orlandis imaginary language(1990), to lead the learners to drink, swim pleasantly and take advantage of the large river of renewable waters that is a fluid language (ORLANDI, 1990). For this purpose we proposed to bring to the classroom, as an analysis and investigation object, something that was from the own students interest and that turned up the Portuguese teaching language process more attractive, relevant and meaningful to them: the online language (also known as netspeak). Our main goal is to put forward pedagogical strategies to work with an online language in benefit of the students linguistics and discursive competency development. Our initial intentions were, indeed, beyond that. Why not trying to work the linguisticsstudentseducation demystifying many myths related to the online language usage? We believed, and we could prove that it was possible. Moreover, that it was feasible to teach important normative grammar topics and highlight the previous knowledge that the research individuals had about our standard language and its convention through online language systematic study. This research is of qualitative nature and was developed in a public school called Joaquim Nabuco, in Divinópolis (MG), with thirty-six students from the ninth grade of Elementary school. In order to elaborate it, we used the sequence teaching method, suggested by Aguiar Jr. (2005). The research goals were achieved fully what proves that the Portuguese language classes can and must be more attractive and interesting to the students. Especially making use of linguistic topics, which they are already familiar with and make sense to the students learn them.